Consumers' purchase intention of rapid COVID-19 tests - Klender Aimer Cortez Alejandro; Martha Rodríguez García; Christian Reich (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - This research aims to analyse the variables related to the purchase intention of COVID-19 rapid tests in Monterrey, Mexico's metropolitan area. Design/methodology/approach - The chosen method was probit regression. The results show that purchase intention depends on the consumer's perceived value and the perception of having a potential contagion and/or presenting symptoms related to the virus. Regarding limitations, the sampling method used in this investigation is a nonprobabilistic convenience approach delivered through a digital platform, which may not be the first option in other contexts. Findings - The findings indicate that the probability of the purchase intention of rapid COVID tests increases when consumers perceive symptoms of the disease and when they have higher education or are female rather than concerning price or income, as suggested by classical demand theory. Research limitations/implications - Probabilistic sampling was impossible due to the difficulty of collecting surveys during the COVID-19 pandemic. Instead, a nonprobabilistic sample of a representative random selection of different zip codes from the responses received was considered. Originality/value - The originality of the paper is its contribution to consumer behaviour during the COVID-19 pandemic in a Latin American context.
Keywords: D11; M2; M3; 330; Rapid COVID-19 tests; Purchase intention; Mexico; Probit; Symptomatology